Electrolyte disorders in athletes - Michał Rogulski; Yauheniya Patarocha; Aleksandra Ślusarska; Jolanta Mędyk; Paulina Błasiak; Małgorzata Wirkijowska; Patryk Mikołajec; Ruslan Huk; Barbara Bilecka; Jakub Wirkijowski (Quality in Sport)
The majority of reviews on sports nutrition issues focus on macronutrients - carbohydrates, proteins and fat, often disregarding substances such as sodium, potassium, calcium and magnesium. Through the literature, it is clear that there are not enough reviews that focus entirely on the effects of electrolytes mentioned above, in particular on endurance sports. Dyselectrolytemia has been related to health and performance issues in athletes. Moreover, it was scientifically proven that one of the reasons for the development of muscle cramps (EAMC) and hyponatremia (EAH) is electrolyte imbalance.That is why, we create this systematic review in order to report extensively on the role of electrolyte consumption in endurance and ultra-endurance athletes, the connection between the quantity consumed and the development of pathological disorders, the effectiveness of concurrent hydration, and whether an imbalance of this substance contributes to EAH and EAMC.